Prevalence of vitamin D deficiency in people with learning disability: A systematic review. (28th June 2019) - Walton, Catherine; Isaac, Andrew; Kerr, Mike
Accessible Summary: People with learning disability have more health problems in comparison to people without learning disability. Low levels of vitamin D in the body is called vitamin D deficiency. This can increase the chance of bone disease, falls and broken bones. This article has reviewed the research evidence from the last 16 years about vitamin D deficiency for people with learning disability. The research shows that people with learning disability have an equal, and possibly higher, chance of vitamin D deficiency. More research is needed to confirm these findings. In order to find out more about how many people with learning disability have vitamin D deficiency, a much larger study is needed. Abstract: Background: \inequality and unmet needs. Vitamin D deficiency can increase the risk of bone disease, muscle weakness and fractures. The aim of this systematic review is to assess for the prevalence of Vitamin D deficiency in people with learning disability. Method: The "Preferred Reporting Items for Systematic Reviews and Meta‐analyses" checklist was followed where possible. Results: Eight studies were included in the qualitative synthesis. The quality of the studies was assessed utilising the "Appraisal of Cross‐sectional Studies" tool. The prevalence of inpatients with learning disability and deficient vitamin D levels ranged from 41% to 92%. This is equal to, and likely higher than, the rate for institutionalised adults in the UK. 49%–77% of individuals with learning disability living in the community had inadequate vitamin D levels. In comparison to the general population, this is provisional evidence to suggest that people with learning disability could have an increased risk of inadequate vitamin D levels. Conclusion: Due to the low number of studies, and the heterogeneous populations of the included studies, firm conclusions could not be drawn. However, the results show that people with learning disability have at least an equal risk of vitamin D deficiency in comparison to the general population. There is provisional evidence to suggest that the prevalence could be higher for people with learning disability, and therefore, there is a need for further population‐based studies.